Curiosity as a moderating variable between Impulsivity and Entrepreneurial Orientation - Boada-Grau, Joan; Vallejo-Vélez, Mauricio; Serrano-Fernández, María-José; Sánchez-García, José Carlos; Boada-Cuerva, Maria; Assens-Serra, Jordi; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2021)
The objective of the present study is to analyze whether the variable Curiosity is a moderating variable between Impulsivity and Entrepreneurial Orientation. The multi-occupational sample of 883 Spanish and Colombian employees (49% men, 51% women) was obtained through non-probabilistic sampling. The data collected were processed with the SPSS 23.0 program. Statistically significant correlations were found among all the research variables except for Functional Impulsivity. Finally, empirical evidence indicates that Curiosity-D plays a moderating role between Dysfunctional Impulsivity and Entrepreneurial Orientation in the sense that Curiosity-D (understood as a quantitative variable) affects the intensity of the relationship between Dysfunctional Impulsivity (predictor variable) and Entrepreneurial Orientation (criterion variable).